223k views
0 votes
Use either long division or synthetic division to solve:

(2i^4 +-6i³+-25i² +31i+-30)/(i +-5)

User SnehalK
by
6.3k points

1 Answer

5 votes

Answer:


\textsf{Quotient}: \quad 2i^3+4i^2-5i+6


\textsf{Simplified Quotient}: \quad 2-7i

Explanation:

Long division method

  • Divide the first term of the dividend by the first term of the divisor, and put that in the answer.
  • Multiply the divisor by that answer, put that below the dividend.
  • Subtract to create a new dividend.
  • Repeat.

Given rational expression:


(2i^4-6i^3-25i^2 +31i-30)/(i -5)

Solve using long division:


\large \begin{array}{r}2i^3+4i^2-5i+6\phantom{)}\\i-5{\overline{\smash{\big)}\,2i^4-6i^3-25i^2 +31i-30\phantom{)}}}\\{-~\phantom{(}\underline{(2i^4-10i^3)\phantom{-b00000000000.)}}\\4i^3-25i^2+31i-30\phantom{)}\\-~\phantom{()}\underline{(4i^3-20i^2)\phantom{))))))))))))}}\\-5i^2+31i-30\phantom{)}\\-~\phantom{()}\underline{(-5i^2+25i)\phantom{........}}\\6i-30\phantom{)}\\-~\phantom{()}\underline{(6i-30)\phantom{}}\\0\phantom{)}\end{array}

Therefore, the quotient is:


2i^3+4i^2-5i+6

Imaginary number rule


i^2=-1

Simplify the quotient:


\implies 2i^3+4i^2-5i+6


\implies 2i^3+4(-1)-5i+6


\implies 2i^3-4-5i+6


\implies 2i^3-5i-4+6


\implies i(2i^2-5)+2


\implies i(2(-1)-5)+2


\implies-7i+2


\implies 2-7i

User Nffdiogosilva
by
6.1k points